Haemangioma of tongue: A rare case report - Sachin Khanduri; Deepak Agrawal; Garima Varshney; Nidhi Singh (Wolters Kluwer Medknow Publications, 2015)
Vascular anomalies include a wide range of tumors and malformations. Among vascular anomalies, hemangioma is the most common. Hemangioma is considered as hamartomatous lesion, and half of these have predilection for head and neck region, but rarely seen in the oral cavity. Here, we report a case of hemangioma in the posterior third of the tongue in a 10-year-old female, which appeared localized well defined, reddish pink and lobulated mass with well-defined margins on intra-oral examination. A well-defined homogeneously hyperechoic space occupying lesion (measuring = 4.4 cm × 4.2 cm) seen on ultrasonography which showed abnormally increased vascularity on color Doppler suggesting a vascular etiology. Further evaluation was done on contrast enhanced computed tomography scan and magnetic resonance imaging, which confirms its vascular nature and diagnosed as a case of hemangioma.